Large electrostrictive coefficient with high electro‐strain dominated by modified ergodic state in BNT‐based solid solutions. Issue 3 (5th November 2020) - Liu, Xinyu; Han, Jihui; Huang, Yanli; Yin, Jie; Wu, Jiagang
Abstract: For ferroelectric electrostrictors, shifting their Curie temperature T C to the ambient temperature is an effective way to enhance their electrostrictive effect. However, the enhanced electrostrictive coefficient Q 33 in this way is often accompanied with an inferior electro‐strain. In this work, by introducing CaZrO3 /BaZrO3 as the special kind of solid solution, with an effective regulation on the ergodic state, we simultaneously realize a larger room‐temperature electrostrictive coefficient Q 33 ( 0.04337 m 4 /C 2 ) with a superior electro‐strain ( 0.41%) in Bi0.5 Na0.5 TiO3 ‐based relaxor ferroelectric ceramics. The ions substitution with larger radius in either A‐site or B‐site of perovskite structure tends to facilitate the evolution from ferroelectric tetragonal phase P4mm to relaxor tetragonal phase P4bm along with the decrease in polarity in crystal, thereby shifting the transition temperature T F‐R below room temperature. As a result of the effective regulation on the ergodic state, a large electro‐strain with low hysteresis, just like electrostrictors, is successfully realized in BNT‐based ferroelectric ceramics. Our investigation provides an effective way to simultaneously enhance the electrostrictive coefficient Q 33 and electro‐strain for practical applications in precisely controlled displacement. Abstract : (a) Electrostrictive coefficient Q33 values versus applied electric field, and S‐E curves under different electric field in the inset picture of BZ15 sample. (b) P4bm content and tetragonality c/a ratio with regard to CaZrO3 or BaZrO3 content. Comparison of lead‐contained, BT‐based, BNT‐based materials and this work against their (c) square of polarization and electro‐strain and (d) electro‐strain and electrostrictive coefficient Q33.